Analisis Proses Bisnis pada Dinas Perdagangan Kota XYZ dengan Menggunakan Business Process Management Lifecycle - Hendy Maulana Jaya Saputra; Deya Elisda Marviainyda; Riska Ayu Larasatu; Muhammad Zabarij Almasz Addaffa; Lovinta Happy Atrinawati (LPPM ITK, 2020)
The XYZ City Trade Office is a government organization that is engaged in regulating the stability of staple food through trade activities in XYZ City. This study aims to identify the existing business processes at the XYZ City Trade Office, in addition to being identified, this study will also conduct an analysis and improvement and redesign of the business processes currently being implemented by the XYZ City Trade Office. The steps taken to identify business processes are by conducting interviews related to the duties and functions of each entity and the Office to stakeholders in the XYZ City Trade Office. The methodology used to identify, describe, analyze and redesign business processes is the Business Process Life Cycle (BPM Lifecycle). The identification results are 36 business processes, and 3 of them are export business processes, import business processes, and processes Business Can Send and Evaluate. In all three business processes further evaluation and analysis are carried out. The analysis and evaluation is to first describe the business process in the form of business process modeling notation (BPMN) using bizagi modeller, then measure the quality of business processes, and analyze weaknesses, and compare with the duties and functions of the Ministry of Trade of the Republic of Indonesia, so that improvements to the process for the third the business process. Improvements for the Export and Import business processes are by adding oversight processes at the shipping stage, and business process improvements Conducting Shipment and Evaluation is by removing the activities of Giving Delivery News. Keywords: Business Process, BPMN, BPM Lifecycle, Bizagi Modeller